Communication Strategy in Strengthening Da'wah for the Muallaf Community in North Sumatra - Suci Ramadhani; Muaz Tanjung (Fakultas Dakwah Institut Agama Islam Sunan Giri Ponorogo, 2023)
Many factors cause a person to decide to become a convert (muallaf). In the case of converts in Tiganderket District, Karo Regency, they still have problems and various problems in living their new faith. The Peduli Muallaf Karo Community is one of the social communities fostering converts in the Karo District. Of course, an effective communication strategy is needed to overcome the various problems experienced by converts when practising the religion they have just believed in, especially in terms of coaching. This study aims to analyze the role of Peduli Muallaf Karo Community, coaching programs, communication strategies used by the Peduli Muallaf Karo Community, and the motivation and effectiveness of converting converts conducted by the Ka Peduli Muallaf Karo Community in Tiganderket District, Karo Regency. This study used a qualitative research method with a descriptive approach. The data collection technique used in this study was observation/field study, interviews, and data analysis through documentation supported by theories from literature studies. The informants in this study were the Peduli Muallaf Karo Community managers, namely the head of Leaders, DPC administrators, and the converts coaches. The results of the study show that the communication strategy used by the Peduli Muallaf Karo Community in fostering converts in Tiganderket District, Karo Regency is relevant to the communication strategy put forward by R. Wayne Peace et al., namely: First, To secure understanding, in this case, the Peduli Muallaf Karo Community uses a local language approach to create mutual understanding and mutual understanding between mentors and converts. Second, To establish acceptance, the Peduli Muallaf Karo Community conducts coaching using lecture methods, question and answer, group discussions, and learning while playing methods. Third, To motivate action, namely, the Peduli Muallaf Karo Community held a special contest for converts as material for evaluating the preacher's performance as well as motivation for converts to continue studying Islam seriously. Namely, the Peduli Muallaf Karo Community conducts coaching using lecture methods, question and answer, group discussions, and learning while playing. Third, To motivate action, namely, the Peduli Muallaf Karo Community held a special contest for converts as material for evaluating the preacher's performance as well as motivation for converts to continue studying Islam seriously.